ANALISIS POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN KEPRIBADIAN ANAK SEKOLAH DASAR - Ardyaningrum, Heny; Banun Havifah Cahyo Khosiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The family environment consisting of father and mother is the first educator for children. The formation of a child's personality is obtained from an early age from family environmental education. Parents' behavior will be seen and implemented in their lives so that parenting styles affect the growth of children's character. This study aims to describe the influence of parenting style given to children in shaping their personality. The subjects of this study were fifth grade students in elementary schools with an age range of 11-12 years. The research method used is a qualitative method with a descriptive approach. Data were obtained by interviewing the parents of research subjects and observational data using a random sampling technique consisting of 8 students. In the results of this study it was concluded that there was a significant relationship between parenting style and the formation of the character of their children. Good parenting will form a good personality and be liked by the environment. While the wrong parenting style will shape the character of the child who is not good. Parents are expected to be able to apply good parenting in order to create good children's character for themselves and their environment.